2002
DOI: 10.1088/0953-8984/14/49/311
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of core shell iron iron oxide nanoparticles

Abstract: We present studies of the structural and magnetic properties of core-shell ironiron oxide nanoparticles. α-Fe nanoparticles were fabricated by sputtering and subsequently covered with a protective nanocrystalline oxide shell consisting of either maghaemite (γ -Fe 2 O 3 ) or partially oxidized magnetite (Fe 3 O 4 ). We observed that the nanoparticles were stable against further oxidation, and Mössbauer spectroscopy at high applied magnetic fields and low temperatures revealed a stable form of partly oxidized ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 32 publications
(56 reference statements)
4
83
0
1
Order By: Relevance
“…Iron oxalate could be a good candidate to diminish these disadvantages; it is used as a reducing reagent to provide the reducing atmosphere for the synthesis system as well as a coordination ligand to reduce the concentration of free iron ions in aqueous solution. Analogous to previous reports for citrate [10,11] and iron/iron oxide core-shell nanoparticles [12][13], iron oxalate ions could form a shell around each magnetite particle, raising in this way the energy required for the particles to agglomerate, and, consequently, stabilizing the corresponding colloidal suspension.…”
Section: Introductionsupporting
confidence: 58%
“…Iron oxalate could be a good candidate to diminish these disadvantages; it is used as a reducing reagent to provide the reducing atmosphere for the synthesis system as well as a coordination ligand to reduce the concentration of free iron ions in aqueous solution. Analogous to previous reports for citrate [10,11] and iron/iron oxide core-shell nanoparticles [12][13], iron oxalate ions could form a shell around each magnetite particle, raising in this way the energy required for the particles to agglomerate, and, consequently, stabilizing the corresponding colloidal suspension.…”
Section: Introductionsupporting
confidence: 58%
“…In earlier work [17] we reported that the XPS spectra of iron nanoparticles removed from storage or synthesis solution and introduced into the spectrometer without air exposure have a significant metallic signal, while air exposure of 1 min (or less) can significantly decrease or remove the metallic character as seen in the 2p region of the iron photoelectron spectra. In contrast, iron core/shell particles reported in work by Kuhn et al [20] were stable with time and environmental exposure. A time dependence of the properties of nanoparticles may limit the areas of their possible application.…”
Section: Time-dependent Properties Of Fe Nanoparticlesmentioning
confidence: 65%
“…Furthermore, the high magnification TEM image of MtZVI-6 ( Figure 3(c)) clearly shows the iron oxide shells on the iron cores, where the iron oxide shells are brighter than the iron cores resulting from their different massthickness contrasts. It is worthy to note that the iron oxide shells have an almost invariable thickness of 3 nm independent of the particle size, which can be explained by the Caberra-Mott theory as some studies referred [12,14,15]. According to this theory, upon the initial attachment of oxygen onto the surface of iron and the formation of a thin oxide layer, the electron tunnels through the thin oxide layer and ionizes the oxygen, leading to an electrical field between the iron and the surface of the oxide layer.…”
Section: Montmorillonite Supported Zerovalent Iron Nanoparticlesmentioning
confidence: 97%